Do children allocated to different methods of complementary feeding introduction have distinct food preferences and flavor acceptance in the first years of life? A randomized clinical trial - Renata Oliveira Neves; Elma Izze da Silva Magalhães; Cátia Regina Ficagna; Paula Ruffoni Moreira; Christy Hannah Sanini Belin; Larissa de Oliveira Silveira; Rogério Boff Borges; Leandro Meirelles Nunes; Juliana Rombaldi Bernardi (PLoS ONE, 2025)
This study aimed to analyze the food preferences and flavor acceptance among children allocated to different methods of complementary feeding (CF) introduction in the first years of life. This randomized clinical trial (RCT) involved three distinct groups of children regarding the method of CF introduction: Parent-Led Weaning (PLW); Baby-Led Introduction to SolidS (BLISS); and Mixed (both PLW and BLISS methods). The intervention occurred at 5.5 months old, and food preferences were analyzed between the ages of 12–35 months using the Food Preferences Questionnaire and the Taste Acceptance Test. The analysis was performed by intention-to-treat, using Pearson’s chi-square test, Mann-Whitney test and Poisson regression. A d irected a cyclic g raph (DAG) was used to define the covariates. A total of 140 mother-infant pairs were randomized for the study (PLW n = 45; BLISS: n = 48; and Mixed: n = 47). Of them, 132 completed the Food Preferences Questionnaire, and 92 attended the Taste Acceptance Test. In unadjusted analysis, the prevalence of preferences for foods with a predominant sour taste was higher in the Mixed method compared to the PLW [Crude prevalence ratio (PR): 1.23; 95% CI: 1.03–1.47; p = 0.020]. However, after adjusting for covariates, this association did not remain statistically significant (Adjusted PR: 1.15; 95% CI: 0.94–1.41; p = 0.173). There was a significant association between the consumption of the solutions and their respective hedonic reactions in most of the offered tastes (sweet: p < 0.001; sour: p = 0.029; salty: p = 0.005; umami: p = 0.026). In addition, food preferences related to the bitter taste were associated with the higher acceptance of the solution with the same taste in unadjusted analysis (Crude PR: 1.12; 95% CI: 1.1–1.25, p = 0.046), but this association did not remain significant in the adjusted analysis (Adjusted PR: 1.16; 95% CI: 0.99–1.37; p = 0.069). In conclusion, infants in the Mixed group showed higher sour taste preference than PLW, though not significant after adjustment.